The International Prohibitions on the Military use of Artsakh’s Cultural Property by Azerbaijan - Tigranyan, Armine (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
During wars, cultural heritage is particularly vulnerable to deliberate attacks and acts of intolerance, as starkly demonstrated during the 44-day war initiated by Azerbaijan in 2020, the blockade of the Lachin Corridor, and the complete depopulation of Artsakh due to military operations in 2023. In armed conflicts, the use of monuments and their surrounding cultural landscapes for military purposes – such as shelters, ammunition depots, combat bases, observation posts, command centers, or deployment hubs for armed forces – poses a significant threat to heritage protection. During and after the 2020 war, numerous churches, community cultural centers, and educational institutions in Artsakh were repurposed by Azerbaijan for military use. This repurposing undermined the primary cultural, spiritual, historical, educational, and aesthetic functions of these heritage sites. By altering their roles to serve military purposes – effectively turning them into “military objects” – their spiritual and cultural significance is disrupted. Moreover, this transformation violates the protections afforded by the Hague and Geneva Conventions, as well as international humanitarian law, which safeguard cultural heritage as a civilian asset. Converting heritage sites for military purposes compromises their inviolability, making them more susceptible to damage or destruction. Despite the norms of international humanitarian law, incidents of damage and destruction to Artsakh's monuments due to their military use by Azerbaijan have not ceased. On the contrary, they continue to escalate, further endangering the cultural heritage of the region and, by extension, the world.
Keywords: Art